Dampak Alokasi Bantuan Modal dan Tenaga Kerja Keluarga terhadap Kesejahteraan Rumah Tangga Petani di Nusa Tenggara Timur - Ferdy Adif I. Fallo; Bonar Marulitua Sinaga; Sri Hartoyo; Pantjar Simatupang (Jurnal Agro Ekonomi, 2018)
English East Nusa Tenggara is the province with the highest poverty prevalence in Indonesia. One of the government's efforts to overcome poverty in the area is the capital assistance program for farm households. This research aimed to analyze the impacts of capital support and household labor allocation on the welfare of farm households in East Nusa Tenggara. The survey for data collection was conducted from in South Central Timor and Kupang Regencies of East Nusa Tenggara Province February to July 2017 with samples of 118 farmer households. Data analysis was conducted by developing an econometric simulation model based on farm-household economic theory. The results showed that increasing capital aid allocation for livestock business decreased the welfare, but increasing investment for livestock business, allocation of capital support for nonfarm business, and allocation of family labor for nonfarm business in single case had an impact on improving the welfare of farmer's household. The best combination consisted of increasing investment for livestock business, allocation of capital support for nonfarm business, and family labor allocation for nonfarm business. Increasing the allocation of family labor for nonfarm business is an important policy because it singly or in combination had an impact on improving the welfare of farm households.IndonesianNusa Tenggara Timur merupakan provinsi dengan prevalensi kemiskinan tertinggi di Indonesia. Salah satu upaya yang dilakukan pemerintah untuk mengatasi kemiskinan di daerah tersebut adalah program bantuan modal kepada rumah tangga petani. Penelitian bertujuan untuk menganalisis dampak alokasi bantuan modal dan tenaga kerja rumah tangga terhadap kesejahteraan rumah tangga petani. Survei pengumpulan data dilaksanakan di Kabupaten Timor Tengah Selatan dan Kupang Provinsi Nusa Tenggara Timur pada bulan Februari hingga Juli 2017 dengan sampel sebanyak 118 rumah tangga petani. Analisis dilakukan dengan membangun model simulasi ekonometrik berbasis teori ekonomi rumah tangga petani. Hasil penelitian menunjukkan bahwa peningkatan alokasi bantuan modal untuk usaha ternak menurunkan kesejahteraan, namun peningkatan investasi untuk usaha ternak, alokasi bantuan modal untuk usaha non pertanian, dan alokasi tenaga kerja keluarga untuk usaha non pertanian secara tunggal berdampak meningkatkan kesejahteraan rumah tangga petani. Kombinasi terbaik ialah kombinasi peningkatan investasi untuk usaha ternak, alokasi bantuan modal untuk usaha nonpertanian, dan alokasi tenaga kerja keluarga untuk usaha nonpertanian. Peningkatan alokasi tenaga kerja keluarga untuk usaha nonpertanian merupakan kebijakan yang cukup penting karena secara tunggal maupun kombinasi berdampak meningkatkan kesejahteraan rumah tangga petani.